ANALISIS SIMPANG TIGA BERSINYAL TUGU ADIPURA KOTA PAYAKUMBUH MENGGUNAKAN METODE MKJI 1997 - Ifansul Ilham; Masril Masril; Ishak Ishak (Ensiklopedia Research and Community Service Review, 2022)
AbstractThe rapid growth in the number of vehicles each year is not accompanied by an increase in road infrastructure. The population of Payakumbuh which is increasing from year to year causes the need for transportation equipment to increase. 36,960 vehicles and cars pass through the streets of Payakumbuh every day. Of the 36,960 vehicles, 70% were two-wheelers and 30% were four-wheelers. Comparing road conditions and transportation facilities will cause traffic congestion, especially during peak hours, and will have an impact on increasing pollution, travel time, costs, social and actual working time. The actual capacity of all intersections is 4106 pcu/hour, the degree of saturation of all intersections can be DS = 0.25 < 0.6 so the road category is smooth. The delay time for all these intersections is Dtot = 4.66 sec/pcu and the highest queue probability at all intersections is 13.61% Keywords: Signalized intersections, road lanes, intersection performance, queuing opportunities,   degree of saturation, intersection capacity